Implementing a Simple Care Bundle Is Associated With Improved Outcomes in a National Cohort of Patients With Ischemic Stroke. Issue 4 (April 2015) - Turner, Melanie; Barber, Mark; Dodds, Hazel; Murphy, David; Dennis, Martin; Langhorne, Peter; Macleod, Mary-Joan
<x xml:space="preserve">Abstract</x> Background and Purpose— Further research is needed to better identify the methods of evaluating processes and outcomes of stroke care. We investigated whether achieving 4 evidence-based components of a care bundle in a Scotland-wide population with ischemic stroke is associated with 30-day and 6-month outcomes. Methods— Using national datasets, we looked at the effect of 4 standards (stroke unit entry on calendar day of admission [day 0] or day following [day 1], aspirin on day 0 or day 1, scan on day 0, and swallow screen recorded on day 0) on mortality and discharge to usual residence, at 30 days and 6 months. Data were corrected for the validated 6 simple variables, admission year, and hospital-level random effects. Results— A total of 36 055 patients were included. Achieving stroke unit admission, swallow screen, and aspirin standards were associated with reduced 30-day mortality (adjusted odds ratio [95% confidence interval]: 0.82 [0.75–0.90], 0.88 [0.77–0.99], and 0.39 [0.35–0.43], respectively). Thirty-day all-cause mortality was higher when fewer standards were achieved, from 0 versus 4 (adjusted odds ratio [95% confidence interval], 2.95 [1.91–4.55]) to 3 versus 4 (adjusted odds ratio [95% confidence interval], 1.21 [1.09–1.34]). This effect persisted at 6 months. When less than the full care bundle was achieved, discharge to usual residence was less likely at 6 months (3 versus 4 standards; adjusted odds ratio [95% confidence interval], 0.91 [0.85–0.98]). Conclusions— Achieving a care bundle for ischemic stroke is associated with reduced mortality at 30 days and 6 months and increased likelihood of discharge to usual residence at 6 months.